The centrality of God in human knowledge - Al-Hadlaq, Afaf Muhammad (Research Journal in Advanced Humanities, 2024)
The present study aims to study the inadequacy of human thinking strategies and knowledge to prove the existence of God. It highlights the contributions of early Muslim scholars in organizing human knowledge and addressing its challenges. These scholars emphasized the importance of basing cognitive perceptions on the knowledge of God and the central role of belief in His existence in cognitive research across various disciplines. This research explores the importance of God in the acquisition and development of knowledge. It focuses on the relationship between individual cognitive research, encompassing scientific, experimental, and ethical domains, and the fundamental principles that underlie it. Additionally, it examines the possibility of establishing a moral framework that is not reliant on religious beliefs. Furthermore, the research investigates the coherence of the atheistic perspective on the natural world, particularly in its utilization of scientific methods to uncover truth without considering the existence of God.